LIPID AND SILVER NANOPARTICLES GELS FORMULATION OF TEMPEH EXTRACT - Felicia Satya Christania; Rini Dwiastuti; Sri Hartati Yuliani (Sanata Dharma University, 2019)
Tempeh extract is used in this study as an active ingredient in lipid nanoparticles and reductant in silver nanoparticles because tempeh is an authentic Indonesian food ingredient and is known to have the main content of isoflavones. Gel preparations were chosen to increase the acceptability and stability of lipid and silver nanoparticles. This research is aimed to formulate lipid nanoparticle gel formulations with tempeh extract as active substances and silver nanoparticle gel formulations with tempeh extract as bioreduction. Lipid nanoparticles were made from soy lecithin phospholipids by heating at 600C and sonication method for 30 minutes then the tempeh extract was added just before sonication. Silver nanoparticles were made by adding tempeh extract to the AgNO3 solution at 900C for 30 minutes. The average particle size of tempeh extract lipid nanoparticles was 130.03 nm and silver nanoparticle was 94.76 nm. The average viscosity of tempeh extract lipid nanoparticles gel was 4.02 d.Pa.s and silver nanoparticles was 4.22 d.Pa.s. The average spreadability of tempeh extract lipid nanoparticles gel was 4.37 cm and silver nanoparticles was 4.05 cm. The average pH value of tempeh extract lipid nanoparticles was 7.70 and silver nanoparticles was 7.33.